Managing software development projects : formula for success - Whitten, Neil (John Wiley & Sons New YorkUS, 1995)
Presents a practical guide to identifying and resolving many major problems prevalent in software projects. Targets project managers, leaders and participants. Covers likely problem areas such as: project discipline, scheduling, tracking, product objectives, product specifications, development testing, and vendor relationships.